Plasma Levels of MicroRNA-155 Are Upregulated with Long-Term Left Ventricular Assist Device Support. Issue 5 (September 2017) - Wang, Teresa; O'Brien, Emily C.; Rogers, Joseph G.; Jacoby, Daniel L.; Chen, Michael E.; Testani, Jeffrey M.; Bowles, Dawn E.; Milano, Carmelo A.; Felker, G. Michael; Patel, Chetan B.; Bonde, Pramod N.; Ahmad, Tariq
Abstract : Left ventricular assist device (LVAD) therapy unloads the failing heart but exposes the human body to unique pathophysiologic demands such as continuous blood flow and complete univentricular support, which are associated with increased risk of adverse clinical outcomes. MicroRNAs (miRNAs) are 22–23 nucleotide RNAs involved in regulation of multiple biologic processes including the pathogenesis of heart failure (HF). Thus, measurement of miRNAs may have potential in both diagnostics as circulating biomarkers and in therapeutics for targeted interventions. We examined 23 distinct miRNAs that have previously been shown to play a role in HF pathogenesis and measured them in 40 individuals both before continuous-flow LVAD implantation and at a median of 96.5 days after implantation. Quantitative real-time polymerase chain reaction was performed for miRNA amplification, and 19 miRs were included in statistical analysis. Wilcoxon signed-rank tests were used to compare within-patient median relative quantification values pre- and post-LVAD placement. The median age of patients was 67 years, and 57.5% were at Interagency Registry for Mechanically Assisted Circulatory Support level 1–2. After LVAD support, only miR-155 was found to be statistically significant ( p < 0.002), with an upregulation in plasma expression levels with LVAD support, which persisted regardless of the direction of change in serial HF biomarker levels. MicroRNA-155, which has been shown to play a central role in inflammation and neovascularization, was upregulated with long-term LVAD support. If validated by future studies, miR-155 may help further inform on underlying LVAD physiology and has a role as a therapeutic target in this patient population.